Tolerance in Prophet's Sunnah - Ahmadova, Konul (Scholarya Demo Journal of Ruby, 2018)
Islam as a religion denies pressure and obligation. Muslims contended people by this principle promoting Islam under the leadership of Mohammad. During the Prophet’s time, people with different opinions and beliefs were not assimilated, freedom of religion and conscience was guaranteed by the state. It is necessary to improve relations between people to ensure peace in society. Respect for people with different ideas and beliefs is one of the signs of moderate behavior. This kind of behavior brings the hearts of people closer and stimulates the spirit of solidarity. The Prophet reacted patiently to the events that had taken place, and tried to win the hearts of his opponents. If the Messenger of Allah had harshly and unkindly responded to events, there would be problems with the Islam’s propagation. Islam would not be a universal religion today and would remain as a local one. In our article, we tried to investigate the Prophet’s moderate behavior towards his companions, polytheists and hypocrites, Jews and Christians, women and children, enemies and captives using examples from verses of the Holy Quran and the Prophet’s hadith.